Practical Haskell : a real world guide to programming - Mena, Alejandro Serrano (Apress, 2022)
Get a practical, hands-on introduction to the Haskell language, its libraries and environment, and to the functional programming paradigm that is fast growing in importance in the software industry. This updated edition includes more modern treatment of Haskell's web framework and APIs. This book contains excellent coverage of the Haskell ecosystem and supporting tools, including Cabal and Stack for managing projects, HUnit and QuickCheck for software testing, WAI and Elm to develop the back end and front end of web applications, Persistent and Esqueleto for database access, and parallel and distributed programming libraries. You’ll see how functional programming is gathering momentum, allowing you to express yourself in a more concise way, reducing boilerplate, and increasing the safety of your code. Haskell is an elegant and noise-free pure functional language with a long history, having a huge number of library contributors and an active community. This makes Haskell the best tool for both learning and applying functional programming, and Practical Haskell, Third Edition takes advantage of this to show off the language and what it can do. Free source code available on the Apress GitHub page for this book.